Towards understand spirituality in Bioethics: DOI:10.15343/0104-7809.200731.2.1 - Fabri dos Anjos, Márcio (2007)
The study aims to gather elements to point out the place of spirituality in Bioethics. It explains the different concepts ofspirit, through the history of thought, and verifies how the term opens to a plurality of conceptualizations. But such plurality does notundo the incisiveness of its questions, for these always arrive at the present time, deserving a place in the agenda of thinkers. The studyalso shows some main concepts of spirituality that derive from conceptions of spirit. It discusses the reason for a place for spiritualityin Bioethics; and, affirming that it is not any spirituality that is adequate to Bioethics, seeks to delineate characteristics that make itadequate.